Effects of drying temperature on the properties of starch in pasta. (June 2021) - Masato, Ohmura; Kentaro, Matsumiya; Tatsuro, Maeda; Akio, Fujita; Yukako, Hayashi; Yasuki, Matsumura
Abstract: The effects of manufacturing process and drying temperature on the properties of starch in pasta were investigated. Starch was isolated from durum wheat semolina, raw pasta, and pasta dried under low temperature, high temperature, and very high temperature. The following measurements were carried out on the extracted starch samples: protein content, ash, amylose content, resistant starch, starch damage, swelling power, amount of solubilized starch, X-ray diffraction spectral analysis, gelatinization temperature, granule size distribution, compression behavior of the gels, and the amount of starch granule-associated protein. The starch isolated from each sample had different physicochemical properties. Starch isolated from raw pasta formed a soft gel and had a low amount of starch granule surface-bound protein compared to starch isolated from semolina. In contrast, increasing the drying temperature of pasta increased the hardness and brittleness of gels formed by the extracted starch, and increased the amount of starch granule surface-bound protein. These results suggest that the amount of starch granule surface-bound protein may be an indicator of starch-protein interaction, which affects the physical properties of extracted starch gels. Highlights: Starch isolated from different pasta samples had different physicochemical properties. Starch gel from very high temperature-dried pasta was harder than from raw pasta. Drying temperature affected the increase in starch granule-bound protein.